Trophic status and phytoplankton diversity of two dam ponds in Eastern Cameroon (Central Africa) - Tenkeu, Janvier Kengne; Tuekam Kayo, Raoul Polycarpe; Tchapgnouo, Joseph Guy Nzieleu; Tchakonte, Simeon; Kamdem, Gwladys Joelle Mogue; Medjo, Pascale Banga; Kueppo, Eric Joselly Kouedem; Edoa, François Désiré Owona; Tsane, Cecile Rita Boudem; Togouet, Serge Hubert Zebaze (International Journal of Environment, Agriculture and Biotechnology, 2021)
A study aimed to determine the level of water pollution and phytoplankton diversity of two dam ponds (Ngaikada and Kpokolota) in Bertoua city was conducted from March 2016 to April 2017 using a monthly sampling frequency. Water samples were collected at surface directly using a 1L polyethylene vials and at 1.5 m depth using a 6L Van Dorn bottle. Physicochemicals analyzes were carried out according to the standard methods of APHA and Rodier, while the harvesting of phytoplankton organisms was done by direct sampling and analyzed by the Utermôhl method. The results of the physicochemicals analyzes reveal no significant difference (P ˃ 0.05*) from surface to depth, high temperature (26.18 ± 1.40°C; 26.29 ± 1.01°C), low transparency (48.57 ± 17.15 cm; 51.43 ± 11.51 cm), high levels of orthophosphates (4.05 ± 3.38 mg/L; 4.15 ± 3.52 mg/L) and oxidability (8.49 ± 6.40 mg/L; 8.10 ± 6.68 mg/L) and high levels of chlorophyll'a' (33.65 ± 24.66 µg/L; 43.67 ± 22.97 µg/L) respectively for Ngaikada and Kpokolota ponds. These characteristics classify these water bodies as hypereutrophics. Biological analyzes have shown that these ponds are quite diversified with 136 and 143 species identified in Kpokolota and Ngaikada respectively. The specific richness, the abundance and the density of phytoplankton organisms recorded at the surface were significantly higher (P ˂ 0.05*) than those at 1.5 m depth. Rehabilitation processes such as control of nitrogen compound flows by purifying waste water from plantations and households, cutting aquatic plants and cleaning mud from ponds should be quickly put in place for a resumption of aquaculture activities.